Regulating finance: who rules, whose rules? - Harris, Stephen L. (2004)
This project has embedded in it an explanation of the structural and relational power transmission process stemming from "micro-actions" in global financial relations. This paper is about domestic policy adaptation in international and domestic finance and how it occurs. The fundamental contention of this paper is that the way to understand power in global finance is to provide an answer to the question: who makes the rules in finance - state actors or nonstate actors? The answer to this question is problematic in the IPE literature because of both the enormous influence of finance in the councils of the industrial democracies and the information asymmetries that favor power in finance. Finance, it is argued, has the determining influence on the rules governing its industry. The dependent variable in this analysis is the policy output - the regulation and liberalization decisions of states. The behaviors of the state and of other policy actors in the policy process are the independent variables. - Reproduced.
Keywords: Finance